Preoperative Metal Patch Testing and Titanium Bar Use Criteria in Nuss Procedure: A 56-Patients' Cohort Study - Pereira-Nunes, Joana; Vasconcelos-Castro, Sofia; Fontoura-Matias, José; Preto-Gomes, Nuno; Marinho-Cunha, Ana; Soares-Oliveira, Miguel (European Journal of Pediatric Surgery, 2022)
Introduction Nuss procedure is the main reason for metal implants use by pediatric and thoracic surgeons. There is an ongoing debate on how to avoid allergic complications. Herein we describe our 8-year experience with systematic preoperative metal patch testing and our selective titanium bar use in Nuss procedure.Materials and Methods This is a single center retrospective observational cohort study of patients who underwent the Nuss procedure from 2013 to 2020. Preoperative metal patch testing was done in all cases. Criteria for titanium bar utilization were: a positive test for a major component of the stainless-steel bar; or a positive metal patch test and a positive history of atopy, food or metal allergy, or previous allergic reaction to an implant or device.Results In total, 56 patients were included. Most were male (91.1%) with a median age of 15.0 (13.0–22.0) years old. 19.6% had a positive preoperative metal patch test and 54.5% of these had no personal history of atopy. Stainless-steel bars were used in 27.3% of those patients and titanium bars were used in 72.7%. One patient had a documented minor allergy reaction. None of the 56 patients required early bar removal.Conclusion Our study suggests that routine preoperative allergy testing and a judicious use of titanium bar are safe and avoid metal allergic complications.
Keywords: metal allergy; Nuss procedure; patch testing; pectus excavatum; titanium bar